The ties that bind : transatlantic abolitionism in the age of reform, c. 1820-1865 - Oldfield, J. R. (John R.) (Liverpool Studies in International Slavery LUP Ser., 2020)
The Ties that Bind explores the close affinities that bound together anti-slavery activists in Britain and the USA during the middle decades of the nineteenth century, shedding important new light on the emergence of a vibrant and broad-based political culture that forced abolition to the centre of public debate.